Deracemization of Secondary Alcohols by using a Single Alcohol Dehydrogenase. Issue 8 (1st March 2016) - Karume, Ibrahim; Takahashi, Masateru; Hamdan, Samir M.; Musa, Musa M.
Abstract: We developed a single‐enzyme‐mediated two‐step approach for deracemization of secondary alcohols. A single mutant of Thermoanaerobacter ethanolicus secondary alcohol dehydrogenase enables the nonstereoselective oxidation of racemic alcohols to ketones, followed by a stereoselective reduction process. Varying the amounts of acetone and 2‐propanol cosubstrates controls the stereoselectivities of the consecutive oxidation and reduction reactions, respectively. We used one enzyme to accomplish the deracemization of secondary alcohols with up to >99 % ee and >99.5 % recovery in one pot and without the need to isolate the prochiral ketone intermediate. Abstract : Detour to the S product : Deracemization of secondary alcohols catalyzed by a single alcohol dehydrogenase is achieved through a nonstereoselective oxidation of racemic alcohols to ketones, followed by a stereoselective reduction catalyzed by the same alcohol dehydrogenase. The amounts of acetone and 2‐propanol are varied to optimize the course of the tandem reaction.